Análise proteômica de Paracoccidioides brasiliensis após estresse oxidativo - Fernandes, Rosiane Rodrigues (2017)
Paracoccidioides brasiliensis is a thermodymorphic fungus, the etiological agent of Paracoccidioidomycosis, a systemic mycosis of high incidence in Latin America. During the infectious process, this fungus is subjected to oxidative stress, produced by host defense cells. Therefore, we sought to analyze the proteomic responses of the fungus when exposed to oxidative stress. Menadione is a compound that decreases the viability of yeasts of Paracoccidioides brasiliensis. The main results were the induction of antioxidant enzymes, such as superoxide dismutase, cytochrome c peroxidase, thioredoxin and peroxisomal catalase, enzymes that help the fungus to fight reactive oxygen species. In addition, proteins involved in metabolic pathways such as glycolysis, tricarboxylic acid cycle and glyoxylate cycle had increased expression, demonstrating a possible remodeling of fungus metabolism. There was the induction of enzymes of the pentose phosphate pathway, which has a prominent role in cells under oxidative stress, since it is an important mechanism producing NADPH (nicotinamide adenine dinucleotide phosphate), an electron donor relevant to counteract the deleterious effects of reactive species of oxygen Heat shock proteins were also upregulated during the oxidative stress to which the fungus was exposed. In this work we investigated the response of a member of the species Paracoccidioides brasiliensis, Pb339 to oxidative stress, including the adaptive mechanisms of this fungus to this condition caused in vitro or by the defense system promoted by the host.